Impact of Using the INTUSTEL Model in Creative Thinking and the Acquisition of Performing Some of the Football Skills by Students - Entethar Faroq Allyas Soran; Stefan Jajo Marzena Garash (Indonesian Journal of Physical Education and Sport Science)
Study purpose. To investigate the impact of applying the traditional lesson on creative thinking and acquisition of performing some of the football skills among the control group students. To explore the effect of applying the INTUSTEL model on creative thinking and acquisition of performing some of the football skills among the experimental group students. The experimental method was adopted to meet the research requirements.